2012
DOI: 10.1016/j.visres.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Male and female faces are only perceived categorically when linked to familiar identities – And when in doubt, he is a male

Abstract: Categorical perception (CP) is a fundamental cognitive process that enables us to sort similar objects in the world into meaningful categories with clear boundaries between them. CP has been found for high-level stimuli like human faces, more precisely, for the perception of face identity, expression and ethnicity. For sex however, which represents another important and biologically relevant dimension of human faces, results have been equivocal so far. Here, we reinvestigate CP for sex using newly created face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 26 publications
9
67
1
Order By: Relevance
“…The dissonance we experience while looking at this image indicates that we have strong expectations about the basic structural properties of a face that cannot help but influence our perception (see Hancock & Foster, 2012). Bülthoff, 2012;Cellerino, Borghetti, & Sartucci, 2004) that has also been reported in chimpanzees (de Waal & Pokorny, 2008). A similar 'male bias' has also been found for body shape (Johnson, Iida, & Tassinary, 2012), hands (Gaetano, van der Zwan, Blair, & Brooks, 2014) and biological motion (Troje, Sadr, Geyer, & Nakayama, 2006).…”
Section: Bias In the Perception Of A Person's Sexsupporting
confidence: 65%
See 3 more Smart Citations
“…The dissonance we experience while looking at this image indicates that we have strong expectations about the basic structural properties of a face that cannot help but influence our perception (see Hancock & Foster, 2012). Bülthoff, 2012;Cellerino, Borghetti, & Sartucci, 2004) that has also been reported in chimpanzees (de Waal & Pokorny, 2008). A similar 'male bias' has also been found for body shape (Johnson, Iida, & Tassinary, 2012), hands (Gaetano, van der Zwan, Blair, & Brooks, 2014) and biological motion (Troje, Sadr, Geyer, & Nakayama, 2006).…”
Section: Bias In the Perception Of A Person's Sexsupporting
confidence: 65%
“…A similar 'male bias' has also been found for body shape (Johnson, Iida, & Tassinary, 2012), hands (Gaetano, van der Zwan, Blair, & Brooks, 2014) and biological motion (Troje, Sadr, Geyer, & Nakayama, 2006). It has been suggested that, in the history of humans, misclassifying a man as female has generally proved to be potentially more dangerous than misclassifying a woman as male (Armann & Bülthoff, 2012). A similar ''better safe than sorry'' heuristic has also been invoked in the context of the bias for direct gaze (Mareschal et al, 2013b) and other social judgments (Haselton & Nettle, 2006;Johnson et al, 2012).…”
Section: Bias In the Perception Of A Person's Sexmentioning
confidence: 79%
See 2 more Smart Citations
“…This type of task is based on the existence of the categorical perception effect, which occurs when the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 perception of differences between categories is enhanced at the expense of our perception of incremental changes in the stimulus within a category (Pollak and Kistler, 2002). This categorical perception effect can be evidenced using an imaging-morphing procedure which consists of creating stimuli that vary along continua between discrete categories: (Kiffel et al, 2005, Angeli et al, 2008, Armann and Bülthoff, 2012. Referring to studies on categorical perception, we chose to use an identification task in which participants had to press a button when they felt familiar with the face that was presented.…”
Section: A N U S C R I P Tmentioning
confidence: 99%